2021
DOI: 10.1088/1755-1315/756/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic content and antioxidant activity of an edible Aroid, Colocasia esculenta (L.) Schott

Abstract: Colocasia esculenta (L.) Schott is an edible aroid from the family of Araceae. It is a tuber crop which is known for its variety of cooking preparation. This study aimed to evaluate the Total Phenolic content (TPC) and antioxidant activities by using 2,2-diphenyl-1-picrylhydrazyl radicals (DPPH) scavenging assay. Methanol fraction showed the highest TPC, whereas the extract obtained using 95% ethanol showed the highest inhibition in DPPH scavenging assay and IC50 values of 308 µg/mL. These results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Due to temperature exposure, reductions in the phenolic and flavonoid profiles occur mainly because of rupturing of the cell structure, which results in relocation and loss of phenolic contents (Barimah et al, 2017). The polyphenol compounds estimated in our learning agree with the previously mentioned ranges (Faizy et al, 2021; Nur‐Hadirah et al, 2021) and were higher than the previously reported findings.…”
Section: Resultssupporting
confidence: 91%
“…Due to temperature exposure, reductions in the phenolic and flavonoid profiles occur mainly because of rupturing of the cell structure, which results in relocation and loss of phenolic contents (Barimah et al, 2017). The polyphenol compounds estimated in our learning agree with the previously mentioned ranges (Faizy et al, 2021; Nur‐Hadirah et al, 2021) and were higher than the previously reported findings.…”
Section: Resultssupporting
confidence: 91%
“…Colocasia leaves, also known as taro leaves, are rich in bioactive chemicals that possess potent antioxidant properties, which make them effective against both biotic and abiotic stress, as evidenced by Nur-Hadirah et al [76]. The total phenolic content (TPC) of Colocasia leaves has been extensively studied, and they have been found to contain approximately 250.23 mg gallic acid equivalent (GAE) per 100 g of fresh weight (FW) of TPC [64].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…When taro antioxidants are combined, they may have either synergistic or antagonistic effects (Ribeiro Pereira et al, 2020). Nur‐Hadirah et al (2021) studied the total phenolic content and antioxidant activity of taro and concluded that due to the presence of bioactive chemicals taro can potentially be a natural source of antioxidants.…”
Section: Therapeutic Potential Of Taromentioning
confidence: 99%
“…The antioxidant capacity of taro corm was determined to be 452 ± 72 mM TEAC/100 g and 244 ± 73 mM TEAC/100 g based on the radical-scavenging activity against ABTS and DPPH, respectively(Simsek & El, 2015).Few taro research studies proceed beyond TAC determination and phytochemical group categorization to determine specific compounds within the aforementioned class, and also their quantities in the plant(Eleazu, 2016;Kumar & Sharma, 2017) The antioxidants in the taro matrix have been discovered and studied, but predicting the effect of a particular molecule on the human body remains a difficult task in this field of study. When taro antioxidants are combined, they may have either synergistic or antagonistic effects(Ribeiro Pereira et al, 2020) Nur-Hadirah et al (2021). studied the total phenolic content and antioxidant activity of taro and concluded that due to the presence of bioactive chemicals taro can potentially be a natural source of antioxidants.…”
mentioning
confidence: 99%